2001
DOI: 10.1071/rd00107
|View full text |Cite
|
Sign up to set email alerts
|

Influence of neonatal estrogens on rat prostate development

Abstract: Brief exposure of rodents to estrogens during early development alters prostate branching morphogenesis and cellular differentiation in a dose-dependant manner. If estrogenic exposures are high, these disturbances lead to permanent imprints of the prostate, which include reduced growth, differentiation defects of the epithelial cells, altered secretory function and reduced responsiveness to androgens in adulthood. This process, referred to as neonatal imprinting or developmental estrogenization, is associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
102
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 45 publications
3
102
0
3
Order By: Relevance
“…In the adult mouse VP, ER␣ is not detectable in the epithelium. Because adult VP epithelium is devoid of ER␣, the current view is that imprinting is mediated by stromal ER␣ (1,5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the adult mouse VP, ER␣ is not detectable in the epithelium. Because adult VP epithelium is devoid of ER␣, the current view is that imprinting is mediated by stromal ER␣ (1,5).…”
Section: Discussionmentioning
confidence: 99%
“…branching morphology ͉ immunohistochemistry ͉ androgen receptor ͉ proliferation ͉ 5␣-androstane-3␤,17␤-diol E xposure of neonatal mice to the nonsteroidal estrogen diethylstilbestrol disturbs prostatic development, alters epithelial cell differentiation, and predisposes mice as they age to prostatic hyperplasia and dysplasia analogous to human prostatic intraepithelial neoplasia (1)(2)(3). This delayed effect of a brief neonatal exposure to estrogens is called imprinting.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, studies of animals in which one or both oestrogen receptors (ERa, ERb) have been inactivated using transgenesis in mice (Couse & Korach 1999). The precise physiological role(s) played by oestrogens in development of the male reproductive system is still unclear, but the prevailing impression gained from the aforementioned studies is that excessive exposure to oestrogens, and consequent disruption of the androgenoestrogen balance, can cause permanent malformations (Arai et al 1983, Toppari et al 1996, Prins et al 2001b, Rivas et al 2002 and predispose to further aberrant changes in later life (Cunha 2001, Prins et al 2001b.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in rats treated neonatally with diethylstilboestrol (DES), have shown impaired development of the epithelium and relative overgrowth of stromal tissue in the epididymis , vas deferens , seminal vesicles , and prostate (Prins et al 2001b, during or soon after the cessation of treatment. These gross structural changes are associated with reduced expression of the androgen receptor (AR; Prins 1992, Prins & Birch 1995, 2001, and with induction of abnormal expression of ERa , Prins et al 2001b.…”
Section: Introductionmentioning
confidence: 99%